JASA PENGIRIMAN UANG OLEH ALFAMART DI INDONESIA MENURUT UNDANG-UNDANG NOMOR 3 TAHUN 2011 TENTANG TRANSFER DANA - Muhammad Mahdi Firdaus; Asep Syarifuddin Hidayat; M Yasir (JOURNAL of LEGAL RESEARCH, 2021)
The purpose of this study was to determine the form of Alfamart's legal responsibility as the organizer of money transfer or fund transfer activities in terms of several laws and regulations governing the legal responsibilities of the fund transfer organizer. The Law is Law Number 3 of 2011 concerning Fund Transfers and other laws governing the obligations, rights and responsibilities of Alfamart as the organizer of fund transfer activities in force in Indonesia. Whereas in the United States, this kind of legal responsibility is regulated in the Electronic Fund Transfer Act (15 USC 1693 et seq) and the Electronic Fund Transfer Act (15 USC 1601 note) in Title IX.This research uses empirical normative legal research using the statute approach, horizontal synchronization approach, comparative approach and library research by conducting an assessment of the laws and regulations and related books. with the title of this thesis.The results showed that there are different forms of Alfamart's legal responsibility as the organizer of fund transfer activities, namely in the Electronic Transaction Information Act, the form of legal responsibility for electronic system organizers and electronic transactions is liability based on fault due to negligence. Whereas in the Fund Transfer Act, the form of legal liability is absolute liability without the possibility of defense (defense) from the organizer of the transfer of funds. On the other hand, the form of legal responsibility implemented in the Electronic Fund Transfer Act (EFTA) is a strict liability with the possibility of a defense (defense) and if there is a conflict between the Funds Transfer Act and the Information Act and Electronic Transactions, according to the principle of "lex posteriori derogat lex priori" used is the latest Law, the Funds Transfer Act.